Edukasi Gema Cermat Untuk Meningkatkan Kualitas Penggunaan Obat Tradisional - Bingar Hernowo (ABDIMAS Madani, 2022)
People's mistake in using drugs irrationally is a national problem. Several irrational drug use behaviors are increasingly prevalent, such as buying over-the-counter drugs that are not appropriate for the disease or wrong consumption procedures. It happens also in the Kradenan. Several mothers stated that so far they had taken the medicine according to the advice of neighbors and close people without carefully reading the use and how to use it. This condition is supported because so far they have only received education about drug management but have not received knowledge about how to carefully choose and use drugs. In accordance with the problems experienced by the partners above, the service provider presents a solution by providing Gema Cermat education to improve the quality of drug use so that people can make independent decisions about the selection and use of drugs carefully and thoroughly. Education is carried out through a lecture model using poster media and the Gema Cermat manual, followed by a Forum. The activity was conducted on 20 may 2022. The results of the activity evaluation show that there is an increase in knowledge about drug use information after service activities are carried out